1963
DOI: 10.1063/1.1729511
|View full text |Cite
|
Sign up to set email alerts
|

Heusler Alloys

Abstract: The results are given of comprehensive measurements on the magnetic and crystallographic properties of the ferromagnetic Heusler alloys Cu2MnAl, Cu2MnIn, Cu2MnSn, Cu2MnGe, Au2MnAl, and the antiferromagnetic alloy Cu2MnSb. The alloys Cu2MnBi and Cu2MnGa are polyphase and the ferromagnetism may be due to binary phases present. The indirect exchange effects which may give rise to ferromagnetism and antiferromagnetism in Heusler alloys are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
1

Year Published

1976
1976
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(57 citation statements)
references
References 8 publications
4
52
1
Order By: Relevance
“…As mentioned in section 1, Cu 2 MnAl in the fully ordered L2 1 state is a strong ferromagnet with a ferromagnetic Curie temperature of 603 K [8] and a magnetic moment of 3.2µ B at room temperature [7]. The ferromagnetism of Cu 2 MnAl results from an indirect type of exchange interaction between the Mn-d orbitals, mediated by intermediate Al orbitals [6].…”
Section: Development Of Magnetic Ordermentioning
confidence: 81%
See 1 more Smart Citation
“…As mentioned in section 1, Cu 2 MnAl in the fully ordered L2 1 state is a strong ferromagnet with a ferromagnetic Curie temperature of 603 K [8] and a magnetic moment of 3.2µ B at room temperature [7]. The ferromagnetism of Cu 2 MnAl results from an indirect type of exchange interaction between the Mn-d orbitals, mediated by intermediate Al orbitals [6].…”
Section: Development Of Magnetic Ordermentioning
confidence: 81%
“…Given the highly ordered L2 1 structure, both Heusler alloys are strong ferromagnets with magnetic moments and ferromagnetic Curie temperatures of 3.2µ B /f.u. [7] and 603 K [8] for Cu 2 MnAl and 5.07µ B /f.u. and 985 K for Co 2 MnSi [9].…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic, electrical, and structural properties in these systems are known to be strongly dependent on both the conduction electron concentration and the chemical order. [26][27][28][29][30] Despite the importance of getting a deeper insight in the electronic structure and the chemical bonding mechanism in these compounds, little research has been performed regarding the magnetic polarization of the conduction electrons and its role in the magnetic ordering. Recently, Uemura et al have reported the results of a combined XAS and x-ray magnetic circular dichroism study performed at the K-absorption edge of both Mn and Cu in these Cu 2 MnM Heusler alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the search for new magnetic materials with uniaxial anisotropy is a key aspect of the ongoing development of spin-electronics materials. [5][6][7][8] Among the desired properties for spin-electronics applications are a high spin polarization at the Fermi level, ideally half-metallicity, [9][10][11][12][13][14][15][16][17] and some noncubic anisotropy. [18][19][20][21] However, the formation of the Ti-Co-Fe-B alloy is limited to nanostructured magnets produced by melt-spinning, and our attempts to produce the corresponding bulk phase by arc melting have been unsuccessful.…”
Section: Introductionmentioning
confidence: 99%